Characterization of Rosemary (Salvia rosmarinus) Essential Oil Obtained by Solvent-Free Microwave Extraction with Kombucha Tea (Anthriscus sylvestris L.) Produced by Adding Guava (Psidium guajava L.) Peel and Pulp - Merve Dilara Gerek; Filiz Yangılar (Journal of Agricultural Sciences)
The study aimed to evaluate the potential of creating a functional beverage by enriching Anthriscus sylvestris (L.) kombucha production with guava peel and pulp, showcasing the variety and richness of the product formulations. This was done due to kombucha being a fermented beverage rich in various bioactive compounds that have significant effects on health and the possibility of enhancing product diversity through different formulations. Thus, the kombucha tea was physicochemical, phytochemical, antioxidant activity, and sensory evaluation during the 15-day fermentation period. The increased acetic acid bacteria and yeast count indicates that Anthriscus sylvestris is a viable substrate for the proliferation of Kombucha symbiotic microbes. Adding guava peel and rosemary oil to kombucha significantly increased its total phenolic, flavonoid, and vitamin C content (P<0.05). Anthriscus sylvestris-guava kombucha has antibacterial properties (zones of inhibition of 18.32 and 17.31 mm against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922, respectively). Moreover, it also provided an inhibitory effect on α-glucosidase and α-amylase, enzymes associated with diabetes. The DPPH, ABTS*+, FRAP, CUPRAC, and ORAC capacities were found to be 66.89-78.90%, 70.83-97.25%, 367-723.15 μmol Trolox/mL, 381.40-460.45 μmol Trolox/mL, and 486.50-737.50 μmol Trolox/mL, respectively. Anthriscus sylvestris kombucha has well-balanced and pleasant sensory properties. These findings indicate that preparing Anthriscus sylvestris kombucha tea with guava may have health effects and that further research is needed to determine potential health benefits.